2023
DOI: 10.1111/ddi.13717
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of species richness and turnover in endemic amphibians of the Guineo‐Congolian rain forest

Abstract: Aim:The African Guineo-Congolian (GC) region is a global biodiversity hotspot with high species endemism, bioclimatic heterogeneity, complex landscape features, and multiple biogeographic barriers. Bioclimatic and geographic variables influence global patterns of species richness and endemism, but their relative importance varies across taxa and regions and is poorly understood for many faunas. Here, we test the hypothesis that turnover in endemic amphibians of the GC biodiversity hotspot is influenced mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 211 publications
0
3
0
Order By: Relevance
“…Despite the high diversity of amphibians found in South America, Central America, and Africa, we found that the percentage of patents related to AMPs granted in these regions is low (South America, 3.7%) or nonexistent. The fact that South America has 15.0% of the natural AMPs described in the literature (Figure A,B and Supporting Information 1.1–1.3) makes these numbers even more surprising.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high diversity of amphibians found in South America, Central America, and Africa, we found that the percentage of patents related to AMPs granted in these regions is low (South America, 3.7%) or nonexistent. The fact that South America has 15.0% of the natural AMPs described in the literature (Figure A,B and Supporting Information 1.1–1.3) makes these numbers even more surprising.…”
Section: Resultsmentioning
confidence: 99%
“…The factors contributing to this research gap in Africa and Central and South America include challenging access to remote areas but mainly a lack of funding for conducting basic and applied research. Thus, as exemplified with Brazil, it is clear that the need for policies incentivizing such studies, including funds and resources, is crucial to unlocking the full potential of these highly biodiverse regions for novel drug discovery and conservation efforts. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Being predominantly used for ecological modelling (Molloy et al, 2014), they represent generalized climate characteristics over a period of time. Bioclimatic variables are widely used in ecological sciences to understand species distributions (Ahmed et al, 2020;Amiri et al, 2020;Yoon & Lee, 2021), assess biodiversity patterns (Hurtado et al, 2020;Nneji et al, 2023) and model ecosystem responses to climate change (Pramanik et al, 2018). Hossell et al (2003) developed a bioclimatic classification for Britain and Ireland, with the objective of identifying areas of significant conservation value by analysing climate variables and bioclimatic indices and demonstrated the significance of bioclimatic variables for highlighting the diversity of habitats, especially in regions characterized by remarkable ecological variability.…”
mentioning
confidence: 99%